Almighty God and the Almighty Dollar: The Study of Religion and Market Economies in the United States. Issue 4 (21st April 2016) - Koenig, Sarah
Abstract: This essay reviews several of the main ways in which scholars of religion have depicted relationships between religion and market economies in the United States. It traces sociological, historical, and ethnographic approaches to the study of religion and market economies, examining how scholars have navigated the tensions between religious declension, on the one hand, and celebration of free market ideals, on the other. It then suggests some directions for further study, including better integration of the studies of material goods, labor, and capitalism with studies of religion and market economies; new studies of religion and finance; greater attention to non‐capitalist systems in U.S. history; and studies that recognize the permeable and co‐constructed nature of religion and market economies.